CtBP-Independent Repression in the Drosophila Embryo - Nibu, Yutaka (American Society for Microbiology, 2003)
There are three mechanisms of transcriptional repression in eukaryotes. The first is quenching, whereby repressors and activators co-occupy closely linked sites and then the repressor inhibits adjacent activators. The second is direct repression, in which repressors block the function of the core transcription complex. The third is competition, in which repressors compete with activators for a common DNA-binding site. Previous studies have shown that the Drosophila melanogaster CtBP corepressor (dCtBP) is essential for the quenching activity of three short-range sequence-specific repressors in the early Drosophila embryo: Krüppel, Knirps, and Snail. Here we demonstrate that dCtBP is dispensable for target enhancers that contain overlapping activator and repressor binding sites. However, it is essential when Krüppel and Knirps repressor sites do not overlap activator sites but are instead located adjacent to either activators or the core promoter. These findings provide evidence that competition is distinct from quenching and direct repression. Quenching and direct repression depend on dCtBP, whereas competition does not.